Consensus on priorities in maternal education: results of Delphi and nominal group technique approaches - Carmen Paz-Pascual; Isabel Artieta-Pinedo; Gonzalo Grandes; ema.Q Group (BMC, 2019)
Abstract Background Maternal education is wide-ranging and covers many areas from pregnancy to the immediate postpartum period and childrearing. However, for it to be effective, more resources need to be assigned to key topics. The goal of this study was to identify and prioritize the most important issues in maternal education, so that specific objectives could subsequently be set and learning outcomes evaluated. Methods We drew up a comprehensive list of topics addressed in existing maternal education programs, based on a systematic review of information obtained from the Internet and the experience of the research team. The topics were presented to a multidisciplinary panel whose members were asked to rate them from 1 to 9, and consensus of opinion was reached using a two-round Delphi survey, with consensus defined beforehand as 80% agreement among panelists in awarding a score of 7, 8 or 9. The most highly-rated topics were then discussed and again prioritized by a multidisciplinary team of healthcare and non-healthcare experts, using a nominal group technique. Results Initially, 650 topics were identified and grouped into 80 categories which were then prioritized by 54 healthcare and non-healthcare experts using a Delphi survey with a study participation rate of around 20%. 63 topics were considered very important, so criteria were restricted and only the 24 highest-scoring selected (95% of agreement on scores ≥7 or 80% of agreement on scores ≥8). Using the nominal group technique, a group of 12 experts identified the following priorities: initiation and establishment of breastfeeding, development of a birth plan, identification of problems and self-care postpartum, nutrition and a healthy lifestyle, options for pain management in labor and birth and characteristics of a normal newborn/looking after a newborn baby. Conclusion This study, with a Delphi study and the Consensus among Experts: the nominal group technique, has succeeded in identifying priority topics in maternal education. We need to assess women's needs in relation to these topics, design an intervention to respond to these needs and evaluate its effectiveness.